Government Policy In Preventing Natural Disasters In Lempang Village, Tanete Riaja District, Barru Regency - Lubis, Iksan Adiputra; Ishak Ismail, Andi Muhammad (Jurnal Info Sains : Informatika dan Sains, 2024)
This study aims to find out government policies in preventing natural disasters in Lempang village, Tanete Riaja District, Barru Regency and to find out the impact of government policies in preventing natural disasters in Lempang village, Tanete Riaja District, Barru Regency. The research method used is a qualitative research method, data sources are obtained by means of observation, interviews, documentation and data analysis techniques by means of data collection, data reduction, data presentation and conclusions. The results of this study show that the government's policy in preventing natural disasters in Lempang village is seen from five indicators, the problem of natural disaster management is caused by natural and human factors. The government's steps are good, the government's policy is good enough, as well as the community's response is good and the effectiveness of the policy impact is good and smoothing community activities in order to achieve community welfare, and for the impact of government policies in preventing natural disasters in Lempang village, namely the impact of policies on the situation of target groups, impacts on other groups, current and future conditions and infrastructure conditions which are the impact of government policies in preventing natural disasters.